Recent advances in the development of gene delivery technologies - Athanasopoulos, Takis (Henry Stewart Talks, 2022)
Major milestones in gene therapies, Ex vivo and in vivo strategies of cell and gene therapy (CGT), The importance of CGT, CGT gene delivery via non-viral approaches, CGT platforms and delivery technologies, The use of viral vectors in gene therapy, Adeno-associated virus vector engineering, Surface engineering lentiviral vectors, The cell and gene therapy strategy of GSK